2001
DOI: 10.1073/pnas.101133498
|View full text |Cite|
|
Sign up to set email alerts
|

A rescue factor abolishing neuronal cell death by a wide spectrum of familial Alzheimer's disease genes and Aβ

Abstract: There is no proof that the HN cDNA represents a gene, that its origin is nuclear, or that the HN peptide is produced in vivo. The information that the long HN cDNA sequence is virtually identical to mitochondrial rRNA should have been put in the Discussion rather than published as supplementary material. The Discussion should have contained the following:The long cDNA [1,567 bp including a poly(A) tail] containing the HN ORF is Ͼ99% identical (1548͞1552) to positions 1679-3230 of mitochondrial DNA (GenBank acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
686
4
11

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 558 publications
(730 citation statements)
references
References 29 publications
29
686
4
11
Order By: Relevance
“…These include humanin , a 24‐amino acid peptide encoded in the 16S rRNA region with strong cytoprotective actions (Hashimoto et al ., 2001) and the recently discovered mitochondrial open reading frame of the 12S rRNA‐c (MOTS‐c), which is a 16‐amino acid peptide that regulates insulin sensitivity and metabolic homeostasis (Lee et al ., 2015). We have recently suggested that MOTS‐c might also be involved in the aging process (Alis et al ., 2015).…”
Section: Mitochondrial‐derived Peptide Mots‐cmentioning
confidence: 99%
“…These include humanin , a 24‐amino acid peptide encoded in the 16S rRNA region with strong cytoprotective actions (Hashimoto et al ., 2001) and the recently discovered mitochondrial open reading frame of the 12S rRNA‐c (MOTS‐c), which is a 16‐amino acid peptide that regulates insulin sensitivity and metabolic homeostasis (Lee et al ., 2015). We have recently suggested that MOTS‐c might also be involved in the aging process (Alis et al ., 2015).…”
Section: Mitochondrial‐derived Peptide Mots‐cmentioning
confidence: 99%
“…91 HN was originally identified as an anti-apoptotic peptide encoded in a cDNA that rescued neuronal cells from apoptosis induced by presenilin mutants associated with familial Alzheimer's disease and by amyloid-beta-protein, during a functional screen of a cDNA library prepared from the brain of an autopsy-confirmed Alzheimer's disease patient. 92 93,94 In this regard, though the 3D structure of Bim-EL is presently unknown, the structures of Bax and Bid are similar, implying that the HN peptide may recognize a conserved structural feature of these proteins. Understanding of the mechanism by which HN suppresses Bax, Bid, and BimEL would be greatly enhanced by the solving of the 3D-structure of a complex of HN with at least one of these proapoptotic proteins.…”
Section: Mechanisms Of Suppression Of Mdpsmentioning
confidence: 99%
“…In this regard, Bcl-2 family members are the central regulators for the mitochondrial membrane permeability (Kroemer and Reed, 2000). Among a long list of Bcl-2 interacting molecules, humanin as well as its homolog, i.e., rattin, is recently identified as a small antiapoptotic peptide in human and rodent cells, respectively (Hashimoto et al, 2001;Caricasole et al, 2002). Through interacting with Bid to inhibit Bax protein activity, humanin has been found to protect neuronal cells from a variety of toxic insults (Guo et al, 2003;Nishimoto et al, 2004).…”
Section: Introductionmentioning
confidence: 99%